Biochemical factors in the blood serum of neuroendocrine tumor patients with carcinoid syndrome - N. V. Lyubimova; Yu. S. Timofeev; A. V. Lebedeva; A. V. Artamonova; I. S. Stilidi; N. E. Kushlinskii (Успехи молекулярной онкологии)
Introduction. Carcinoid syndrome is the most common functional syndrome in patients with neuroendocrine tumors. More than 40 biochemical factors are responsible for the manifestation of carcinoid syndrome, among which serotonin is the most important. The study of biochemical markers of carcinoid syndrome and associated carcinoid heart disease is an important aim of laboratory examination in neuroendocrine tumors patients.Aim. Analysis of levels and diagnostic efficiency evaluation of chromogranin A (CgA), serotonin, pro-brain natriuretic peptide (proBNP) and platelet-derived growth factor (PDGF-BB) in the blood serum of neuroendocrine tumors patients with various clinical manifestations, including carcinoid syndrome and carcinoid heart disease.Materials and methods. 66 patients with neuroendocrine tumors of various localizations were examined (pancreas – 24 cases, small intestine – 21, large intestine – 6, lungs – 10, unkown primary focus – 5). 38 patients had liver metastases. In 43 patients, a clinic of carcinoid syndrome was observed, 16 had signs of carcinoid heart disease. The control group consisted of 30 practically healthy people. Serum levels of CgA, serotonin, and PDGF-BB were determined by enzyme immunoassay in microplate format: Chromogranin A NEOLISA (Eurodiagnostica, Sweden), Serotonin ELISA (IBL, German), and PDGF-BB ELISA Kit (Invitrogen, USA). The proBNP analysis was performed on a Cobas e601 automated analyzer (Roche, Switzerland).Results. In carcinoid syndrome, the medians of CgA, serotonin, and proBNP were the highest, differing statistically significantly from the control group. In patients with G3 tumors, the median PDGF-BB was statistically significantly higher than in controls, in contrast to G1 and G2. The highest diagnostic sensitivity in the general neuroendocrine tumors group was in CgA – 63.6 %, with a specificity of 100 %. In patients with carcinoid syndrome, the highest diagnostic sensitivity was characteristic of serotonin and chromogranin A (79 %), while in patients with CAD clinic, proBNP had the highest sensitivity – 93.8 %.Conclusion. The study revealed the high efficiency of СgA, with the highest sensitivity in common forms and tumors with high biological activity. Serotonin can be used in the diagnosis of carcinoid syndrome, associated with cardiofibrosis development. Pro-brain natriuretic peptide is a highly sensitive and specific marker of carcinoid heart disease. The highest levels of PDGF-BB are associated with a high grade of neuroendocrine tumors malignancy.